(untitled) (Scientific journal of the Fergana State University, 2025)
This study is devoted to the study of effective methods and technologies for improving the teacher’s pedagogical skills in the process of teachin economic sciences. Acquiring modern economic knowledge requires the active participation of students, the formation of skills such as analyzing and solving problem situations. In this process, the teacher’s high pedagogical skills play an important role in students’ dee assimilation#of economic knowledge.